Norm and Essential Norm of Composition Followed by Differentiation from Logarithmic Bloch Spaces to Hμ∞ - Shanli Ye (Abstract and Applied Analysis)
In this note we express the norm of composition followed by differentiation DCφ from the logarithmic Bloch and the little logarithmic Bloch spaces to the weighted space Hμ∞ on the unit disk and give an upper and a lower bound for the essential norm of this operator from the logarithmic Bloch space to Hμ∞.